IN OUR COUNTRY PREVALENCE OF TUBERCULOSIS - Elmurodova Lenara Xudayberdi qizi; Fayzullayev Fazliddin Safar o’g’li (Лучшие интеллектуальные исследования, 2024)
ABSTRACT: One of the urgent tasks of modern medicine is to study the influence of extreme weather and climatic factors on the development of various diseases, including non-specific lung diseases. According to many scientists, it is not individual meteorological factors and a specific type of climate, but the exchange of different climates, that places great demands on the human body's ability to adapt and manage. The changing climate weather factors have a strong impact, causing not only a deterioration in the condition of healthy people and a decrease in their ability to work, but also a significant aggravation of the clinical course of various diseases, including bronchial asthma.